On Preservation of the Order of Flattening by an Induced Diffeomorphism - Zubrilin, K. M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We consider the structure of a smooth curve from the viewpoint of the concept of flattening and establish conditions under which an r-geodesic curve of the base manifold is the projection of the r-geodesic curve in a tangent bundle of the second order. The necessary and sufficient condition under which a 2-geodesic diffeomorphism of affine-connected spaces induces a 2-geodesic diffeomorphism of tangent bundles of the second order is established.